Der Beckengurtel und die hinteren Extremitaten von Eudyptes chrysocome. - Grunert, Paul. ([n.p.] Druck der Buchdruckerei Roitzsch, 1906)
Thesis--Universitaet Leipzig. Includes bibliographical references (pages 19-20). Wood, C.E. Vertebrate zoology, Mode of access: Internet.